Imágenes de rango de la superficie del ojo de la mosca mediante correlación interferométrica (2013)
In this study an initial stage of an investigation about optic areas and signal processing is presented. A description of the reconstruction process of the housefly´s eye surface topography using a microscope with nanometer resolution is explicated. For this reconstruction is implemented the maximal detection method. Using interferometric methods for reconstruction of small samples offers the possibility of analyzing samples without the need to invade with any type of destructive coating like electron microscopes methods. The prospect of topographic eye´s reconstruction offers a possibility to complement the studies on this area, both in the field of entomology and also in the area of engineering for the construction and generation of optical devices. The measures obtained in the reconstruction had an accuracy of 1 nm.